A method to include life cycle assessment results in choosing by advantage (Cba) multicriteria decision analysis. a case study for seismic retrofit in peruvian primary schools - Vázquez-Rowe I. (2021)
This research was partially funded by the Consejo Nacional de Ciencia, Tecnolog?a e Innovaci?n Tecnol?gica del Per?, according to the Convenio de Gesti?n N 232-2015-FONDECYT.